Psychological Changes in the State of the Personality in the Deprivation Conditions of the Self-Quarantine - Vlasenko A.I. (Психолого-педагогические исследования)
In 2020, an event took place in the world community that entailed colossal changes in society – the coronavirus pandemic, which affected all spheres of human life (from economic to social), leading to a crisis not only financial, but also existential. The introduced self-quarantine affected all strata of society, and the created deprivation conditions had a negative impact on the psychological state of the personality, which enhances the relevance of the scientific study of this problem. In general, the work is aimed at analyzing approaches to the phenomenon of deprivation, considering its types and effects on the human body; highlighting the consequences of the self-quarantine, which affected the psychological state of people. As a methodology, a theoretical analysis of the literature on the research problem (retrospective, comparative analyzes, methods of generalization, systematization) was used. The article notes that the self-quarantine generates social deprivation of the personality, described in the psychological and related sciences, and entails many negative consequences for the state of people, to minimize which it is necessary to follow the proposed recommendations.